Is Conversion of a Failed IPAA to a Continent Ileostomy a Risk Factor for Long-term Failure?. Issue 2 (February 2019) - Aytac, Erman; Dietz, David W.; Ashburn, Jean; Remzi, Feza H.
Abstract : BACKGROUND: A continent ileostomy may be offered to patients in hopes of avoiding permanent ileostomy. Data on the outcomes of continent ileostomy patients with a history of a failed IPAA are limited. OBJECTIVE: This study aimed to assess whether a history of previous failed IPAA had an effect on continent ileostomy survival and the long-term outcomes. DESIGN: This was a retrospective cohort study. SETTINGS: This investigation took place in a high-volume, specialized colorectal surgery department. PATIENTS: Patients who underwent continent ileostomy construction after IPAA failure between 1982 and 2013 were evaluated and compared with patients who have no history of IPAA surgery. MAIN OUTCOME MEASURES: Functional outcomes and long-term complications were compared. RESULTS: A total of 67 patients fulfilled the case-matching criteria and were included in the analysis. Requirement of major (52% vs 61%; p = 0.756) and minor (15% vs 19%; p = 0.492) revisions were comparable between patients who had continent ileostomy after a failed IPAA and those who had continent ileostomy without having a previous restorative procedure. Intubations per day (5 vs 5; p = 0.804) and per night (1 vs 1; p = 0.700) were similar in both groups. Our data show no clear relationship between failure of continent ileostomy and history of failed IPAA ( p = 0.638). The most common cause of continent ileostomy failure was enterocutaneous/enteroenteric fistula (n = 14). Six patients died during the study period because of other causes unrelated to continent ileostomy. LIMITATIONS: This study was limited by its retrospective and nonrandomized nature. CONCLUSIONS: Converting a failed IPAA to a continent ileostomy did not worsen continent ileostomy outcomes in this selected group of patients. When a redo IPAA is not feasible, continent ileostomy can be offered as an alternative to conventional end ileostomy in highly motivated patients. SeeVideo Abstract athttp://links.lww.com/DCR/A803 .